Influence of Different Types of Drying Methods on Color Properties, Phenolic Metabolites and Bioactivities of Pumpkin Leaves of var. Butternut squash (Cucurbita moschata Duchesne ex Poir) - Mashitoa, Florence M.; Shoko, Tinotenda; Shai, Jerry L.; Slabbert, Retha M.; Sultanbawa, Yasmina; Sivakumar, Dharini (Frontiers in Nutrition, 2021)
Leaves of pumpkin species var. Butternut squash (Cucurbita moschata Duchesne ex Poir) is a popularly consumed leafy vegetable in the Southern African region. Traditional vegetables are commonly sundried as a method of postharvest preservation during the off-season. However, different drying methods affect the final product's superior quality, functional properties, and bioactivities. Therefore, in this study var. Butternut squash (C. moschata) underwent different drying methods, such as freeze-drying, oven, sun, solar, and microwave-drying to evaluate the color properties, pigments, phenolic metabolites, in vitro antioxidant, and antidiabetic activities. Results indicate that freeze-drying retained the total chlorophyll content green color by reducing the color difference (∆E), improved the concentration of different phenolic metabolites, ascorbic acid content, enhanced the FRAP, ABTS activities and the inhibitory effects of α-glucosidase, and α-amylase. Freeze-dried leaves contained the highest concentrations of quercetin 3-glucoside 7-rhamnoside (rutin), quercetin 3-galactoside, isorhamnetin-3-galactoside-6''-rhamnoside, isorhamnetin-3-O-rutinoside compared to the leaves that underwent four other drying treatments and raw leaves. The OPLS-DA and the UPLC–QTOF/MS and chemometric approach showed that the peak at m/z 609,1441 (quercetin 3-galactoside 7-rhamnoside) separated the freeze-dried leaves of var. Butternut squash (C. moschata) from the other four drying treatments. Therefore, freeze-drying is highly recommended to obtain good quality leaf powders that are rich in functional compounds and bioactive properties, for use as functional ingredients.